Respuesta :

Answer:

2(m + [n)] + [1]

Step-by-step explanation:

(2m) + (2n + 1) =

= 2m + 2n + 1

= 2(m + n) + 1

= 2(m + [n)] + [1]

The simplification of the expression would be equal to 2(m + [n)] + [1].

What is a simplification of an expression?

Usually, simplification involves proceeding with the pending operations in the expression.

Like, 5 + 2 is an expression whose simplified form can be obtained by doing the pending addition, which results in 7 as its simplified form.

Simplification usually involves making the expression simple and easy to use later.

An even plus an odd equals an odd.

[tex](2m) + (2n + 1)\\= 2m + 2n + 1\\= 2(m + n) + 1\\= 2(m + [n)] + [1][/tex]

Learn more about expression ;

https://brainly.com/question/5032318

#SPJ2